2011
DOI: 10.4037/ajcc2011683
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding and Outcomes After Percutaneous Coronary Intervention for ST-Segment Elevation Myocardial Infarction

Abstract: Background Gastrointestinal bleeding is a hemorrhagic complication after primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction (STEMI). Objectives To determine predictors of gastrointestinal bleeding and the impact of gastrointestinal bleeding on outcomes in STEMI patients undergoing primary percutaneous coronary intervention. Methods and ResultsGastrointestinal bleeding occurred in 18 (3.5%) of 519 consecutive patients with STEMI undergoing primary percutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…In the present analysis we found that approximately 8% of STEMI patients developed a GI bleeding within 6 years follow-up. The in-hospital occurrence of GI bleeding has been found to vary between 0.72% in patients undergoing PCI and 3.5% in STEMI patients [19,20]. The higher incidence of GI bleeding in PPCI treated STEMI patients can be explained by the higher prevalence of cardiogenic shock in STEMI patients as compared to unstable angina and NSTEMI [21].…”
Section: Incidence and Predictors Of Gi Bleedingmentioning
confidence: 94%
“…In the present analysis we found that approximately 8% of STEMI patients developed a GI bleeding within 6 years follow-up. The in-hospital occurrence of GI bleeding has been found to vary between 0.72% in patients undergoing PCI and 3.5% in STEMI patients [19,20]. The higher incidence of GI bleeding in PPCI treated STEMI patients can be explained by the higher prevalence of cardiogenic shock in STEMI patients as compared to unstable angina and NSTEMI [21].…”
Section: Incidence and Predictors Of Gi Bleedingmentioning
confidence: 94%
“…Figures 2 and 3 show the risk of mortality and MACE considering unadjusted and adjusted results separately. Eight of the 10 studies reported crude mortality rate 6,10,14,[16][17][18][19]21 which was 13% in patients experiencing a gastrointestinal bleed (96/738) and 3% in the remaining cohort (1898/55 771). There was a significant risk of mortality with gastrointestinal bleeding …”
Section: Access and Non-access Site Bleedingmentioning
confidence: 99%
“…We retrieved 25 relevant studies of patients that underwent PCI (total number of subjects 2 400 645), which evaluated the risk of adverse events with and without major bleeding. 2,[4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Excluded studies are shown in Table II in the Data Supplement. The patient cohort size ranged from 73 to 1 216 759, and 106 490 major bleeding events were recorded (23 studies, 4.5%).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of high doses of aspirin, clopidogrel and low molecular weight heparin in acute STEMI patients and their own perioperative stress response, particularly in patients undergoing PCI surgery, leads to a significantly increased risk of gastrointestinal bleeding (6). Numerous studies have shown its high incidence mainly during the first week of the course of disease (7,8).…”
Section: Discussionmentioning
confidence: 99%